Pengaruh Human Relation Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Bina Marga Kabupaten Aceh Utara - Nurmala Nurmala; Sullaida Sullaida (Jurnal Visioner & Strategis, 2021)
This study aims to see the effect of Human Relations and work motivation on employee performance. The data used in this study were 73 employees of the Highways Office of North Aceh Regency. The analytical tool used is SPSS (Statistical Package for Social Science). The results show that Human Relations has a significant effect on the performance of the North Aceh Highways Office employees and work motivation has a significant effect on the performance of North Aceh Highways Office employees. Human relations and work motivation have a significant effect on the performance of the employees of the North Aceh Highways Office.